Pemanfaatan Teknologi Informasi Dan Keamanan Informasi Dalam Optimalisasi Berkebun Di SMK Swasta Teladan Pematangsiantar Dengan Iot Smart Garden Dan Logika Fuzzy - Ksatria, Iqbal Sandhi; Maradhika, Khafi; Prabowo, Yudi; Irsyad, Muhammad Agil; Gunawan, Indra (CV. ITTC INDONESIA, 2024)
This study aims to optimize the gardening process at SMK Swasta Teladan Pematangsiantar by utilizing information technology and information security through the implementation of an IoT Smart Garden system supported by fuzzy logic. The IoT Smart Garden system functions to monitor the garden's environmental conditions in real-time, including parameters such as soil moisture, temperature, and light intensity. By utilizing sensor technology, the collected data is sent to a cloud-based platform for analysis and processing. Fuzzy logic is used to process the received data, allowing the system to provide more adaptive and intelligent recommendations and automated actions, such as automatically watering plants when soil moisture falls below a certain threshold. This approach not only increases gardening efficiency but also reduces human error in plant care. Additionally, information security is a critical focus in this study to ensure the integrity and confidentiality of the data collected and processed by the IoT system. Various security protocols are implemented to protect the data from potential cyber threats and to ensure that the information generated is reliable. The results of the study show that the use of IoT technology and fuzzy logic significantly enhances productivity and efficiency in gardening activities at SMK Swasta Teladan Pematangsiantar. This system also provides additional benefits such as water and time savings, as well as improved plant quality. Therefore, the implementation of information technology and information security in this IoT-based gardening system can serve as a model for other educational institutions looking to adopt similar technology for their agricultural activities